The Influence of Turbine Output Power on The Efficeincy of The Generator PLTU Sintang (3 x 7 MW) - Lumbantoruan, Pintor S.; Yandri, Yandri; Hie Khwee, Kho (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
A generator is an electrical device that functions as a tool that can convert mechanical energy into electrical energy. Generator efficiency will affect the performance of the PLTU system, the greater the generator efficiency, the better the generator efficiency, therefore generator efficiency is an important thing to maintain the quality of electrical energy that will be distributed to consumers. The aim of this research is to calculate the influence of fluctuating turbine power on generator efficiency using the Steam Property mobile application. Based on the average value obtained, the efficiency of the unit 1 power plant is 87.46%, with an average load of 4.26 MW and actual turbine power of 4.88 MW. The lowest efficiency display occurred on day 1 with an efficiency of 78.83%, while the highest efficiency value occurred on day 5 with an efficiency of 91.28%. Changes in the load on the generator affect the generator efficiency value which is followed by changes in actual turbine power, where if the load value is close to the actual turbine power value then the efficiency is large and vice versa.